Cloud computing bible - Sosinsky, Barrie A. (Indianapolis, Ind. : Wiley Pub., 2011)
Looks at what cloud computing is and is not, why cloud computing exists, and the value of cloud computing, along with information on cloud computing platforms, infrastructure, services, and security.
Overview: The complete reference guide to the hot technology of cloud computing. Its potential for lowering IT costs makes cloud computing a major force for both IT vendors and users; it is expected to gain momentum rapidly with the launch of Office Web Apps later this year. Because cloud computing involves various technologies, protocols, platforms, and infrastructure elements, this comprehensive reference is just what you need if you'll be using or implementing cloud computing. Cloud computing offers significant cost savings by eliminating upfront expenses for hardware and software; its growing popularity is expected to skyrocket when Microsoft introduces Office Web Apps; This comprehensive guide helps define what cloud computing is and thoroughly explores the technologies, protocols, platforms and infrastructure that make it so desirable; Covers mobile cloud computing, a significant area due to ever-increasing cell phone and smartphone use; Focuses on the platforms and technologies essential to cloud computing; Anyone involved with planning, implementing, using, or maintaining a cloud computing project will rely on the information in Cloud Computing Bible.
Part 3: Exploring Cloud Infrastructures: -- Managing the Cloud: -- Administrating the Clouds -- Management responsibilities -- Lifecycle management -- Cloud management products -- Emerging Cloud Management Standards -- DMTE cloud management standards -- Cloud commons and SMI -- Summary -- Understanding Cloud security: -- Securing the Cloud -- Security boundary -- Security service boundary -- Security mapping -- Securing data -- Brokered cloud storage access -- Storage location and tenancy -- Encryption -- Auditing and compliance -- Establishing identity and presence -- Identity protocol standards -- Windows Azure identity standards -- Presence -- Summary -- Part 5: Understanding Services And Applications: -- Understanding service oriented architecture: -- Introducing Service Oriented Architecture -- Event-driven SOA or SOA 2.0 -- Enterprise Service Bus -- Service catalogs -- Defining SOA Communications -- Business Process Execution Language -- Business process modeling -- Managing and Monitoring SOA -- SOA management tools -- SOA security -- Open Cloud Consortium -- Relating SOA and Cloud Computing -- Summary -- Moving applications to the Cloud: -- Applications in the Clouds -- Functionality mapping -- Application attributes -- Cloud service attributes -- System abstraction -- Cloud bursting -- Applications and Cloud APIs -- Summary -- Working with Cloud-Based Storage: -- Measuring the Digital Universe -- Cloud storage in the Digital Universe -- Cloud storage definition -- Provisioning Cloud Storage -- Unmanaged cloud storage -- Managed cloud storage -- Creating cloud storage systems -- Virtual storage containers -- Exploring Cloud Backup Solutions -- Backup types -- Cloud backup features -- Cloud attached backup -- Cloud Storage Interoperability -- Cloud Data Management Interface (CDMI) -- Open Cloud Computing Interface (OCCI) -- Summary -- Working with productivity software: -- Using Productivity Applications -- Characteristics of productivity software -- Online Office Systems -- Acrobat.com -- Glide Digital -- Google Docs -- Microsoft Office Web Apps -- ThinkFree Office -- Zoho Office Suite -- Summary -- Using Webmail Services: -- Exploring the Cloud Mail Services -- Google Gmail -- Mail2Web -- Windows Live Hotmail -- Yahoo! Mail -- Working with Syndication Services -- RSS and Atom Protocols -- Newsreaders -- News Aggregators -- Summary -- Communicating with the Cloud: -- Exploring Instant Messaging -- Instant messaging clients -- Instant messaging interoperability -- Micro-blogs or Short Message Services -- Exploring Collaboration Technologies -- Using Social Networks -- Features -- List of social networking sites -- Privacy and security -- Interaction and interoperability -- Summary -- Using media and streaming: -- Understanding the streaming process -- Protocols in use -- Cloud computing advantages -- Audio streaming -- Working with VoIP Applications -- Skype -- Google Voice and Google Talk -- Video streaming -- Television in the cloud -- Streaming video formats -- YouTube -- YouTube technologies -- YouTube and the law -- Summary -- Part 5: Using The Mobile Cloud: -- Working with mobile devices: -- Defining the mobile market -- Connecting to the cloud -- Adopting mobile cloud applications -- Feature phones and the cloud -- Using Smartphones with the Cloud -- Android -- Apple iPhone -- App Store -- MobileMe -- iPhone apps hosting services -- Research in Motion BlackBerry -- Symbian -- Windows Mobile -- Summary -- Working with mobile web services: -- Understanding service types -- Mobile interoperability -- Performing service discovery -- Context-aware services -- MEMS -- Location awareness -- Push services -- BlackBerry Push Service -- Lemonade Profile -- Using SMS -- Defining WAP and other protocols -- Performing synchronization -- Summary -- Index.
Title from title screen.
Includes index.
John Wiley and Sons
Keywords: Cloud computing; Web services; Infonuagique; Services Web; Cloud computing; Web services